579 The Impact of Coronavirus 2 (SARS-CoV-2) in Emergency Surgery. Our experience at the General Surgery Department in Queen Elizabeth Hospital, London. (4th May 2021) - Chatzikonstantinou, M; David, M; Pouncey, A; Aljarad, F; Sorelli, P
Abstract: Background: The outbreak of the COVID-19 has had global impact on elective and emergency surgical care. So far, we possess few data to understand the effect of the CoViD-19 on emergency surgery. Aim: To compare the total number of patients who were referred, admitted, and had an emergency operation under General Surgery (GS) between March and May 2020, to the same period between 2016-19. Method: Retrospective analysis of prospectively collected local data from surgical take lists and operative data obtained from the hospital's Business Intelligence Team. Results: A 22.4% reduction was seen in the referrals per day 15.18+/-2.45 vs. 11.77 +/- 4.54 (2016-9 vs. 2020, mean+/-SD) and a 36% reduction in admissions per day 7.40 +/-1.07 vs. 4.69+/- 2.03 (2016-9 vs. 2020, mean+/-SD). A 55% reduction in the total number of emergency operations during the CoViD-19 outbreak was observed 87 (total, 2020) vs. 194+/-35.96 (mean+/-SD, 2016-19). Conclusions: CoViD-19 had a significant impact on the number of patients presenting to GS. Interestingly, an even greater reduction in operative treatment was also observed. This may reflect reduction in theatre availability or use of a higher threshold for conservative treatment.